2004
DOI: 10.1021/jp046813h
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Extremely Low Temperature Catalytic Dehydrochlorination of 1,1,1-Trichloroethane over Platinum

Abstract: Fast X-ray photoelectron spectroscopy reveals that the efficient catalytic destruction of 1,1,1-trichloroethane occurs over Pt{111} surfaces at temperatures as low as 150 K. Decomposition occurs via rapid, sequential C−Cl bond scission to form an alkylidyne surface intermediate that in turn dehydrogenates above room temperature. Atomic chlorine liberated during dehydrochlorination undergoes efficient reaction with surface hydrogen, resulting in the evolution of gaseous HCl and small amounts of ethane, presumab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Similarly dehalogenation of cis -1,2- and trans -1,2-dichloroethene (DCE) has been reported above 200 K on Pt(111), although a more recent synchrotron study by Cassuto et al found both DCE and 1,1,2-trichloroethene (TCE) simply desorbed at 250 K without any reaction . More recently we have reported that above 130 K dehydrochlorination of 1,1,1-trichloroethane is observed via rapid sequential C−Cl bond scission to form a surface alkylidyne intermediate and HCl. , …”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Similarly dehalogenation of cis -1,2- and trans -1,2-dichloroethene (DCE) has been reported above 200 K on Pt(111), although a more recent synchrotron study by Cassuto et al found both DCE and 1,1,2-trichloroethene (TCE) simply desorbed at 250 K without any reaction . More recently we have reported that above 130 K dehydrochlorination of 1,1,1-trichloroethane is observed via rapid sequential C−Cl bond scission to form a surface alkylidyne intermediate and HCl. , …”
Section: Introductionmentioning
confidence: 71%
“…The latter is attributed to the strong adsorption of hydrocarbon reaction intermediates and irreversible coke deposition; HCl is not believed to play a significant role in catalyst self-poisoning. We have recently shown that there is a delicate balance between low-temperature poisoning by accumulated surface chlorine and high-temperature coking over a model Pt(111) catalyst, which also extends to practical dispersed Pt/γ-Al 2 O 3 catalysts …”
Section: Introductionmentioning
confidence: 76%
“…In contrast, the m Pd NPs produced more ethylene than ethane, i.e., only the polyhedral and multiply-twinned Pd particles approached the desired selectivity (Figure 12). The deactivation of the Pd NPs, induced by the chlorine poisoning of the surfaces, was beneficial for the selectivity (Figures 11a and 12a), but this was more pronounced for the curved (stepped) s Pd NPs [7,10,21,25,110,[112][113][114][115][116]. The stepped surface structures prefer the π adsorption mode, while smooth (111) planes of m Pd NPs favor the di-σ adsorption mode (Figure 10) [95,101,104,106,109,110,112,117,118].…”
Section: Catalytic Application Of Pt and Pd Nps For Tce Hydrodechlorinationmentioning
confidence: 99%
“…In an effort to understand PGM hydrodechlorination catalysts, we used TP-XPS to investigate the thermal chemistry of 1,1,1-trichloroethane (TCA), a common commercial solvent until 2005, over Pt (111). 166 TCA adsorbs non-dissociatively at 100 K, bonding through the three Cl atoms in a vertical geometry akin to ethylidyne. Between 120-200 K, around 60% of chemisorbed TCA undergoes rapid, stepwise C-Cl bond cleavage via CH 3 CCl 2 and CH 3 CCl metastable surface intermediates, liberating atomic chlorine and ethylidyne (Fig.…”
Section: C-x Activationmentioning
confidence: 99%